Design and Docking Studies of Some Novel 1-Phenyl-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indole-3-carboxylic acids as Inhibitors of Human Immunodeficiency Virus Type-1 Reverse Transcriptase - Ashok, P.; Kishore Babu, Kakumanu; Murugesan, S.; Ganguly, S. (Asian Journal of Chemistry, 2012)
Molecular docking is an important tool in QSAR and inhibitor design. In the present study, novel 20 1-phenyl-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indole-3-carboxylic acid analogs were designed and docked into the non-nucleoside inhibitory binding pocket (NNIBP) of human immunodeficiency virus-1 (HIV-1) reverse transcriptase (RT) structure with protein brookehaven database (PDB) ID 1rt2. Autodock 4.0.2 software was used to explore the exact binding conformation of the designed molecules, TNK 651 and standard drug efavirenz. Initially, the docking of the extracted TNK 651 was performed to ensure the validity of docking calculations, reliability and reproducibility of the docking parameters for present study. Autodock was able to reproduce the experimental binding conformation of TNK 651 within acceptable root mean square deviation (RMSD) of 0.56 Å. Next, cross docking experiment was performed using standard molecule Efavirenz with 1rt2 for comparison purpose. Finally, the docking studies of newly designed analogs of 1-phenyl-2,3,4,9-tetraahydro-1H-pyrido[3,4-b]indole-3-carboxylic acids were performed. Among the designed analogs, 2-(2-(2-nitrophenylamino)-2-oxoethyl)-1- phenyl-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indole-3-carboxylic acid (TBB-1-11), 2-(2-(3- nitrophenylamino)-2-oxoethyl)-1-phenyl-2,3,4,9-tetraahydro-1H-pyrido[3,4-b]indole-3-carboxylic acid (TBB-1-10), 2-(2-(2,4-dichlorophenylamino)-2-oxoethyl)-1-phenyl-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indole-3-carboxylic acid (TBB-1-18) and 2-(2-(4-hydroxyphenylamino)-2-oxoethyl)-1-phenyl-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indole-3-carboxylic acid (TBB-1-5) showed significant and comparable binding free energy and predicted inhibitory constant values of -15.10, -13.36, -12.62, -12.57 kcal/mol and 8.60, 160.05, 562.14, 609.94 pM respectively with that of standard drug Efavirenz. These results indicate that, the designed analogs adopt a similar orientation and share the same binding mode as that of some classical non-nucleoside reverse transcriptase inhibitors (NNRTIs) within the active site of NNIBP of HIV-1 reverse transcriptase.